Recommendation systems: A Review - Zaid Mundher (Universitas Khairun, 2025)
Recommendation systems have become one of the most widespread types of systems today, as they have become a necessity and a need. Recommendation systems can be defined as methods for presenting or marketing electronic products (in various forms) to users, with the selection of products based on the user's actual needs. This is achieved through the use of specific algorithms and methods to gauge the user's interest in the suggested products. Recently, the applications of recommendation systems have expanded beyond a single field or aspect, extending into many areas of life and science. Many methods have been developed and improved for building recommendation systems from naive to advanced ones.This study aims to provide a comprehensive overview of recommendation systems: definitions, objectives, and types, including the advantages and disadvantages of each type.